Macrophage pyroptosis and its crucial role in ALI/ARDS - Cai, Yuju; Shang, Luorui; Zhou, Fangyuan; Zhang, Mengqi; Li, Jinxiao; Wang, Shuhan; Lin, Qifeng; Huang, Jianghua; Yang, Shenglan (Frontiers in Immunology, 2025)
Acute lung injury(ALI)/acute respiratory distress syndrome(ARDS) is a severe clinical syndrome characterized by high morbidity and mortality, primarily due to lung injury. However, the pathogenesis of ALI/ARDS remains a complex issue. In recent years, the role of macrophage pyroptosis in lung injury has garnered extensive attention worldwide. This paper reviews the mechanism of macrophage pyroptosis, discusses its role in ALI/ARDS, and introduces several drugs and intervening measures that can regulate macrophage pyroptosis to influence the progression of ALI/ARDS. By doing so, we aim to enhance the understanding of the mechanism of macrophage pyroptosis in ALI/ARDS and provide novel insights for its treatment.